NAVIGATING THE CUMULATIVE EFFECTS OF FAMILY LANGUAGE POLICY DURING CHILDHOOD FOR IMMIGRANT YOUTH IN CANADA - MACCORMAC, MEGAN; MACCORMAC, KATHERINE (Society Register, 2021)
One of the most influential decisions that immigrant parents must make for their children involves establishing a set of rules and norms governing what language(s) they will be raised with and how they will acquire proficiency in the dominant languages of the host society, a process known as family language policy. Such decisions can have long lasting effects for immigrant children into adulthood by influencing their integration into the host society and transition towards adult life. Using retrospective, in-depth interview data collected from young immigrant adults, this study explores the ways that parental decisions made throughout an immigrant child’s life course regarding language use and learning shape their multilingual identity and attitude towards the use of multiple languages in their everyday adult life. Findings suggest that the linguistic decisions parents make in the early years of an immigrant youths’ life have lasting impacts on them in terms of connecting to family members and culture in adulthood. We found that when parents created either a flexible or strict family language policy, such policies produced more positive experiences in the migration and early settlement process for immigrant youth compared to those whose parents did not form a family language policy.